The impact of war in Ukraine on beer industry - Harkavenko, Iryna; Harkusha, Olena O. (My University, 2023)
Russia’s invasion of Ukraine has already heavily impacted both national and world’s industry and beer industry in particular. It has reshaped national economy. Countries reliant on the exports from both Ukraine and Russia suffered as a consequence. Вторгнення Росії в Україну вже сильно вплинуло на обидві країни, світову промисловість і пивну промисловість, зокрема. Це змінило національну економіку. Від цього постраждали країни, які залежать від експорту як з України, так і з Росії.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; пивоваріння; alcohol sales; продаж алкоголю